2022
DOI: 10.1111/os.13569
|View full text |Cite
|
Sign up to set email alerts
|

Does the Level of Syndesmotic Screw Insertion Affect Clinical Outcome after Ankle Fractures with Syndesmotic Instability?

Abstract: Objective: Ankle fractures are often combined with syndesmotic instability, requiring reduction and stabilization. However, the optimal level for syndesmotic screw positioning remains unclear. This study aims to evaluate the effect of different syndesmotic screw insertion levels on postoperative clinical outcomes and determine whether an optimal level exists.Methods: This retrospective study included data from 43 adult patients with acute closed ankle fractures combined with intraoperative evidence of unstable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…1. Анатомический препарат и схема области дистального межберцового синдесмоза: 1 -хрящ; 2 -синдесмотическое углубление; 3 -передняя тибиофибуляная связка; 4 -задняя тибиофибулярная связка; 5межкостная связка [1] Переломы лодыжек -распространенный вид травмы, занимающий третье место по частоте среди переломов нижних конечностей, на него приходится от 5,5 до 7,4 % всех переломов скелета, 25 % из которых ассоциированы с разрывом или повреждением дистального синдесмоза, вызывающими значительные функциональные нарушения в долгосрочном периоде [3][4][5][6][7][8]. Особенно это касается переломов типа C по классификации Вебера, которые всегда ассоциированы с разрывом дистального синдесмоза, а также переломов типа Б по классификации Вебера, высокоэнергетических переломов лодыжек, разрыв синдесмоза среди которых встречается в 37 % случаев [9][10][11][12][13][14].…”
Section: гений ортопедии 2024;30(1)unclassified
“…1. Анатомический препарат и схема области дистального межберцового синдесмоза: 1 -хрящ; 2 -синдесмотическое углубление; 3 -передняя тибиофибуляная связка; 4 -задняя тибиофибулярная связка; 5межкостная связка [1] Переломы лодыжек -распространенный вид травмы, занимающий третье место по частоте среди переломов нижних конечностей, на него приходится от 5,5 до 7,4 % всех переломов скелета, 25 % из которых ассоциированы с разрывом или повреждением дистального синдесмоза, вызывающими значительные функциональные нарушения в долгосрочном периоде [3][4][5][6][7][8]. Особенно это касается переломов типа C по классификации Вебера, которые всегда ассоциированы с разрывом дистального синдесмоза, а также переломов типа Б по классификации Вебера, высокоэнергетических переломов лодыжек, разрыв синдесмоза среди которых встречается в 37 % случаев [9][10][11][12][13][14].…”
Section: гений ортопедии 2024;30(1)unclassified
“…The syndesmosis connects the distal tibia and fibula, and damage to it can cause serious acute and long-term morbidity [ 6 ]. According to estimates, a syndesmotic injury coexists with 13% of all ankle fractures and 20% of fractures that require surgical treatment [ 7 ]. Cedell found that only 1% to 10% of ankle ligament injuries (medial collateral, lateral collateral, and interosseous ligaments) were syndesmotic sprains [ 8 ].…”
Section: Introductionmentioning
confidence: 99%